Virtual reality and virtual environments : a tool for improving occupational safety and health - Grabowski, Andrzej (Occupational safety, health, and ergonomics. Theory and practice., 2020)
"These VR techniques offer a wide range of possibilities for people with disabilities and special needs assisting them in the process of adapting workstations and provide the perfect tools to support the engineering of safer workplace environment"--